Investigation of GaN nanowires containing AlN/GaN multiple quantum discs by EBIC and CL techniques. (14th March 2019) - Piazza, Valerio; Babichev, Andrey V; Mancini, Lorenzo; Morassi, Martina; Quach, Patrick; Bayle, Fabien; Largeau, Ludovic; Julien, François H; Rale, Pierre; Collin, Stéphane; Harmand, Jean-Christophe; Gogneau, Noelle; et al.
Abstract: In this work, nanoscale electrical and optical properties of n-GaN nanowires (NWs) containing GaN/AlN multiple quantum discs (MQDs) grown by molecular beam epitaxy are investigated by means of single wire I ( V ) measurements, electron beam induced current microscopy (EBIC) and cathodoluminescence (CL) analysis. A strong impact of non-intentional AlN and GaN shells on the electrical resistance of individual NWs is put in evidence. The EBIC mappings reveal the presence of two regions with internal electric fields oriented in opposite directions: one in the MQDs region and the other in the adjacent bottom GaN segment. These fields are found to co-exist under zero bias, while under an external bias either one or the other dominates the current collection. In this way EBIC maps allow us to locate the current generation within the wire under different bias conditions and to give the first direct evidence of carrier collection from AlN/GaN MQDs. The NWs have been further investigated by photoluminescence and CL analyses at low temperature. CL mappings show that the near band edge emission of GaN from the bottom part of the NW is blue-shifted due to the presence of the radial shell. In addition, it is observed that CL intensity drops in the central part of the NWs. Comparing the CL and EBIC maps, this decrease of the luminescence intensity is attributed to an efficient charge splitting effect due to the electric fields in the MQDs region and in the GaN base.